PROPOSED WORK PROCESS IMPROVEMENT TO MINIMIZE WASTE WITH 8 WASTE APPROACH - Fauzi, Muchammad; Rahmana, Arief; Suyono, Annisa Maharani; Tiana, Neng Sri; Umar, Muhamad Iqbal Zen (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this study is to analyze activities that do not provide added value and provide suggestions for increased productivity in the IPC division. Research at the PQR company which is engaged in the pharmaceutical business has various wastes in the IPC division. This IPC Division often experiences problems that arise because of waste. For example, the waste that often occurs is the waiting process that often occurs in the production process. The emergence of these problems becomes material for researchers to conduct research using one of the lean manufacturing tools "8 waste". By using Lean Manufacturing, it is hoped that it can solve the problems that occur, Lean Manufacturing is a systematic approach to identify and eliminate waste through a series of improvement activities, the 8 waste method can reduce waste that occurs in the IPC division. The results of identification using the 8 waste method, there are several processes, namely overproduction, waiting for waste, transportation waste, exec processing waste, motion waste, defects, and nonutilized talent waste.